A prospective study on response to treatment of patients with temporomandibular dysfunction: A clinical study - Kashmola, Muhanad Ali Hamdon; Mustafa, Nazih Shaban; Abdul Jabbar, Omar; Mohamed, Robiah; Mohamed Talmizi, Siti Nabilah; Mustafa Al-Ahmad, Basma Ezzat (2018)
Temporomandibular joint disorders (TMD) affect a big proportion of the population. It is multifactorial in origin. The clarification of its associated factors is crucial. Early determination of TMD accompanied with suitable treatment may give good response. The aim of this study is to identify the relationship between demographic parameters, signs and symptoms, diagnosis, detection and treatment with review outcomes. Study sample consists of 71 patients attended Oral Medicine and Oral Pathology clinic. Demographic parameters (age, gender, and profession) were recorded. TMD staging was done based on Wilkes system. Treatment including self-education, occlusal splint, and medication were proposed to patients based on their signs and symptoms. Prosthetic rehabilitation was indicated for free-end extension ridge. Treatment outcomes measure recommended by the International Association of Oral and Maxillofacial Surgeons (IAOMS) was used. Age shows significant relationship with the signs and symptoms of TMD (p <0.05). Association between signs and symptoms, diagnosis and stage of detection with the given treatment (p < 0.05) was acquired. Significant correlation existed between signs and symptoms before and after treatment (r = - 0.452). The stage of detection exhibited significant relationship with review outcome. It was worth noted that the outcome during review visit depended on the treatment given according to the signs and symptoms, which were influenced by demographic parameters (p < 0.05). This study had successfully manifested the relationship between demographic parameters, the signs and symptoms complained by TMD patients, the diagnosis, the detection, treatment proposed with findings during review.